2001
DOI: 10.1136/gut.49.5.636
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 modulates ion secretion and cell proliferation in cultured human small intestinal enterocytes

Abstract: (Gut 2001;49:636-643)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 38 publications
(34 reference statements)
1
16
0
Order By: Relevance
“…1). Previous studies (6,34) showed that supplementing IL-2 in FBS-containing growth media promoted proliferation even at a lower concentration in BN cells, while a biphasic effect was observed in a similar concentration range in IEC 6 cells. This raises the question as to the physiologic levels of IL-2 that might occur in the intestines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Previous studies (6,34) showed that supplementing IL-2 in FBS-containing growth media promoted proliferation even at a lower concentration in BN cells, while a biphasic effect was observed in a similar concentration range in IEC 6 cells. This raises the question as to the physiologic levels of IL-2 that might occur in the intestines.…”
Section: Discussionmentioning
confidence: 99%
“…The specific role of IL-2 in intestinal epithelial homeostasis is not known. In vitro studies using different IEC lines from human and rat show that IL-2 promotes IEC proliferation and ion secretion (2,34). However, IL-2 has also been shown to enhance susceptibility to apoptosis in colonic epithelial cells (44).…”
mentioning
confidence: 99%
“…These early studies found that leukotrienes C4, D4 and E4 stimulated chloride secretion and inhibit sodium and chloride absorption in rat and rabbit ileum mounted in Ussing chambers [136,137]. Ex vivo studies in small intestinal preparations revealed antagonistic effects of cytokines on chloride secretion with IL-2 and IL-15 enhancing cyclic adenosine monophosphate (cAMP)-mediated chloride secretion [120] while IL-4 and IL-10 diminished chloride secretion by reduction of intracellular cAMP [33,100].…”
Section: Ion Channels Regulating Fluid Distributionmentioning
confidence: 98%
“…IL-2 is able to augment endothelial cell proliferation and hence vascularization [156]. Other studies have shown that IL-2 affects enterocyte ion secretion and proliferation [157], and it has also been demonstrated to be an important neuroregulatory molecule implicated in neurite survival and extension, oligodendrocyte proliferation, hypothalamic-pituitary function and analgesia [158].…”
Section: The Il-2/il-2r Pathway In Other Immune Cell Typesmentioning
confidence: 99%